Improving the Nationalism Character of 5-6 Years Old Children through NUPO (Nusantara in Power Point) Media - Diana Prameswari; Amirul Mukminim (Universitas Pendidikan Ganesha, 2025)
Nationalism character refers to an attitude of love for the homeland reflected through appreciation of national values, patriotism, and cultural diversity. However, early childhood understanding of these values remains relatively low amid the rapid development of technology and the increasing flow of globalization. This condition highlights the need for innovative learning approaches that can instill nationalism values in an engaging manner and in accordance with children's developmental characteristics. This study aims to analyze and examine the effectiveness of NUPO media in improving the nationalism character of children aged 5–6 years. The study employed a quantitative approach with a pretest–posttest experimental design. The research subjects consisted of 30 children selected using purposive sampling technique. Data were collected through observation using a nationalism character observation sheet as the instrument, supported by documentation. The collected data were analyzed using a t-test to identify differences in nationalism character before and after the treatment. The results show that the use of NUPO media in the learning process significantly improves children’s nationalism character. This improvement is indicated by changes in observational results between the initial condition and after the implementation of the learning media. These findings suggest that NUPO media is effective as a learning tool for instilling nationalism values in early childhood. The implications of this study indicate that the use of innovative and interactive learning media can serve as a relevant strategy to support the strengthening of character education from an early age.